ANALISIS PROFESIONALISME KINERJA PEJABAT PENATAUSAHAAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH KOTA BANDA ACEH - Cut Yunita Elvira; Meutia Handayani; Ardian Ardian (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to determine the professionalism of the performance of the financial administration apparatus in the Banda Aceh regional work unit by using position analysis and understanding of regional financial management information systems on the performance of the regional financial administration apparatus. The sampling technique in this study is the census method, obtaining 44 respondents. The results show that job analysis and understanding of regional financial management information systems partially have a significant effect on the performance of the financial administration apparatus in the Banda Aceh regional work unit. Furthermore, job analysis and regional financial management information systems understanding have a significant effect on the financial administration apparatus performance in the Banda Aceh regional work unit simultaneously.